Tax structure for consumption and income inequality: An empirical assessment - José Alves; António Afonso (SERIEs - Journal of the Spanish Economic Association, 2019)
In this study, we assess the relationship between several tax items and consumption and income inequality levels. For OECD countries between 1980 and 2015, we use panel data techniques and find tax threshold values regarding inequality levels and consumption. In particular, we obtain threshold values for social security contributions between 9.50 and 11.80% (of GDP), for long-run consumptions, while to promote a reduction in income inequalities we found a 15.51% share of social security contributions over GDP, in both short- and long-term perspectives. Lastly, our results would support higher taxes on firms, in GDP terms, to decrease income inequalities, although that might hamper aggregate consumption.
Keywords: D63; E21; H21; 330; Income inequality; Consumption; Tax thresholds